Pengawasan dan Pengendalian Sumberdaya Perikanan Pada Aktivitas Illegal Fishing di Sulawesi Tengah (Studi Kasus Di WPPNRI 713) - Arwansa, Arwansa; Serdiati, Novalina; Sulistiawati, Dwi (Mitra Sains, 2024)
The main objective of this study is to know the supervision and law enforcement in the management of fisheries resources in WPPNRI 713, Central Sulawesi Province. This research was conducted in September - October 2022. The sample used was a sample of the WPPNRI 713 Fishermen community in Donggala Regency. This study uses a qu(2024)alitative method. Data collection by means of sampling includes observation activities, in-depth interview techniques, questionnaires and documentation studies. Using Descriptive Qualitative data analysis method with percentage distribution tabulation. The results of the research show that the supervision of fish resource management in WPPNRI 713, especially in the province of Sulawesi, has not been maximized, the institutions have not been maximized, the FADs have not been arranged and while the use of fishing gear has shown compliance of around 50% more in accordance with laws and regulations.